2009
DOI: 10.1590/s0102-311x2009001100009
|View full text |Cite
|
Sign up to set email alerts
|

A alimentação saudável na ótica dos adolescentes: percepções e barreiras à sua implementação e características esperadas em materiais educativos

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
41

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 33 publications
2
33
0
41
Order By: Relevance
“…A Brazilian study conducted in the FD, which used the "problematization" methodology with 25 adolescents, indicated the following main barriers for healthy eating: temptation, food taste, parental influence, lack of time, and few choices for healthful snacks at school 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study conducted in the FD, which used the "problematization" methodology with 25 adolescents, indicated the following main barriers for healthy eating: temptation, food taste, parental influence, lack of time, and few choices for healthful snacks at school 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies are consistent on the grounds that food consciousness is related to environmental and family factors, besides state of motivation itself, and not to organic factors. 8,[10][11]17 Among these external factors, the association with living with parents and/or siblings was not expected either, since it is suggested that formal education and parental income, cohabitation time and family routine (not assessed in this analysis) are the major infl uential factors, rather than just the cohabitation characteristics. 14 The data reported in this analysis is useful for possible inferences about the population's eating habits, as poor awareness of food and nutrition refl ects on the consolidation of attitudes and food choices, even under interference from environmental factors hitherto mentioned.…”
Section: Discussionmentioning
confidence: 85%
“…Alves et al (2009) 26 and Assis et al (2014) 23 have observed about 50% pre-intervention accuracy in similar studies with adolescents from MG. Toral (2010) 17 , in a qualitative analysis with 25 adolescents aged 15+ in Brasília (DF), has reported accounts of appropriate general notions of healthy eating, including FV intake (without defi ning recommendations, however). Nevertheless, there were no specifi c national data regarding FV awareness for comparison with the results herein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations